(untitled) (Fiep Bulletin - online, 2016)
Introduction: The demographic transition changed the framework for the control of infectious diseases for the treatment and prevention of morbidity and mortality triggered by chronic diseases. Although this is due to the increase in life expectancy, the current situation of health of the population is far from understanding the full needs of the population, especially those with pediatric, which depend on someone else for their use. Objectives: Conduct literature, systematization and subsequent analysis of the health conditions of children in Brazil. Methods: Literature review aimed to cover socioeconomic, physiologic characteristics, public policy and limiting aspects about the health of the child, in the pre and post natal, as well as throughout their stages of development. The search for publications was conducted electronically, in databases, using descriptors related to the theme, besides the exploitation of bibliographic references of eligible publications to complete reading. The information was arranged systematically, in order to adjust the content to each predetermined theme. Conclusions: Childhood represents a unique and crucial period for shaping the individual, through environmental and social influences that contribute so much to his personality as for your health. The evolution of information systems promoted greater diagnostic and health problems of notifications as well as possible identification and distribution services to the population, such as vaccination. Although public policies providing for the child’s right to access to adequate health and living conditions, the child’s picture in Brazil still requires actions focused on their real needs, made through social practice consists of family, environment and state.